Epinephrine-mediated protein kinase C and Rap1b activation requires the co-stimulation of Gz-, Gq-, and Gi-coupled receptors - Lova, Paolo; Guidetti, Gianni Francesco; Canobbio, Ilaria; Catricalà, Silvia; Balduini, Cesare; Torti, Mauro (Thrombosis and Haemostasis, 2011)
We have recently shown that ADP-induced activation of protein kinase C (PKC) requires the co-stimulation of both P2Y1 and P2Y12 receptors. In this work, we show that inhibition of ADP-mediated phosphorylation of pleckstrin, the main PKC substrate, caused by antagonists of the P2Y12 receptor can be reversed by stimulation of the α2-adrenergic receptor by epinephrine. However, we also observed that addition of epinephrine alone caused a marked phosphorylation of pleckstrin. This effect occurred in the absence of Gq stimulation, as it was not associated to intracellular Ca2+ release. Epinephrine-induced pleckstrin phosphorylation was time- and dose-dependent, and was inhibited by the α2-adrenergic antagonist yohimbin. Phosphorylation of pleckstrin did not occur when platelet stimulation with epinephrine was performed in the presence of the ADP scavenger apyrase, and was suppressed by antagonists of both P2Y1 and P2Y12 ADP receptors. Importantly, no release of dense granules was measured in epinephrine-treated platelets. Addition of epinephrine to platelets was also able to stimulate Rap1b activation. Similarly to pleckstrin phosphorylation, however, this effect was prevented in the presence of apyrase or upon pharmacologic blockade of either P2Y1 or P2Y12 receptors. These results indicate that sub-threshold amounts of ADP in the medium are essential to allow epinephrine stimulation of α2-adrenergic receptor to elicit platelet responses, and reveal a novel synergism among strong stimulation of Gz and sub-threshold stimulation of both Gq and Gi, able to dissociate PKC activation from intracellular Ca2+ mobilisation.
Keywords: Signal transduction; epinephrine; protein kinase C; Rap1b; ADP receptors